Classical Opacity*. - Caie, Michael; Goodman, Jeremy; Lederman, Harvey (Philosophy & Phenomenological Research, 2020)
The article presents the discussion on substitution with putative cases of opacity. Topics include involving equivocation and the sentence being false providing no mid-sentence shift in context; introducing the framework of higher-order logic within the investigation taking place; and providing a precise characterization of Classical Opacitism and developing theories of Classical Opacity based on different ways of responding to the choice point.